2009
DOI: 10.1159/000226594
|View full text |Cite
|
Sign up to set email alerts
|

Population Screening for Genetic Disorders in the 21st Century: Evidence, Economics, and Ethics

Abstract: Background: Proposals for population screening for genetic diseases require careful scrutiny by decision makers because of the potential for harms and the need to demonstrate benefits commensurate with the opportunity cost of resources expended. Methods: We review current evidence-based processes used in the United States, the United Kingdom, and the Netherlands to assess genetic screening programs, including newborn screening programs, carrier screening, and organized cascade testing of relatives of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
92
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 157 publications
1
92
0
2
Order By: Relevance
“…37,38 Ideally, the implementation of NIPD will take all stakeholder views into consideration. Furthermore, health professionals must recognize that their views about prenatal tests may differ from those of the women with whom they discuss testing.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Ideally, the implementation of NIPD will take all stakeholder views into consideration. Furthermore, health professionals must recognize that their views about prenatal tests may differ from those of the women with whom they discuss testing.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, before a general program for all neonates is initiated, the merit of such screening should be explored in well-conducted investigations of defined populations. In general, one can consider populationbased genetic screening if a condition is an important health problem with a latent early symptomatic stage, has a wellunderstood natural history, and there exist accepted treatments with associated facilities for providing diagnosis and treatment (Grosse et al, 2009). These requirements are fulfilled by KS to some extent, but a formal proof of improved long-term adult outcomes is lacking.…”
Section: Screening For Early Diagnosismentioning
confidence: 99%
“…48,49 The clinical utility of genetic testing has been difficult to demonstrate for a variety of reasons, but significant effort is currently being expended to overcome these obstacles. Single-nucleotide polymorphisms implicated in the most powerful GWA studies typically explain only a small fraction of the observed variation for a disease, which partly stems from a combination of methodological and practical limitations.…”
Section: Genetic Testingmentioning
confidence: 99%